2008
DOI: 10.1074/jbc.m803072200
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Light Chain LC8 Negatively Regulates NF-κB through the Redox-dependent Interaction with IκBα

Abstract: Redox regulation of nuclear factor B (NF-B) has been described, but the molecular mechanism underlying such regulation has remained unclear. We recently showed that a novel disulfide reductase, TRP14, inhibits tumor necrosis factor ␣ (TNF␣)-induced NF-B activation, and we identified the dynein light chain LC8, which interacts with the NF-B inhibitor IB␣, as a potential substrate of TRP14. We now show the molecular mechanism by which NF-B activation is redox-dependently regulated through LC8. LC8 inhibited TNF␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 57 publications
2
113
1
Order By: Relevance
“…In response to potent NF-kB activators such as TNF-a, IkBa is phosphorylated at residues Ser 32 and Ser 36 by IKK and subsequently degraded by the ubiquitin-proteasome system (33). Pre- vious studies showed that LC8 blocked IkBa phosphorylation by IKK in TNF-a-treated cells (25). Therefore, we examined the effect of LC8 on IkBa phosphorylation and degradation in BMMs stimulated with RANKL.…”
Section: Lc8 Inhibits Rankl-induced Nf-kb Activationmentioning
confidence: 99%
See 3 more Smart Citations
“…In response to potent NF-kB activators such as TNF-a, IkBa is phosphorylated at residues Ser 32 and Ser 36 by IKK and subsequently degraded by the ubiquitin-proteasome system (33). Pre- vious studies showed that LC8 blocked IkBa phosphorylation by IKK in TNF-a-treated cells (25). Therefore, we examined the effect of LC8 on IkBa phosphorylation and degradation in BMMs stimulated with RANKL.…”
Section: Lc8 Inhibits Rankl-induced Nf-kb Activationmentioning
confidence: 99%
“…The DNA sequence encoding hemagglutinin (HA)-tagged LC8 was amplified via PCR using the pCGN-LC8 vector (25,26) as a template with a forward primer (59-CG GAA TTC ATG GCT TCT AGC TAT CCT TAT GAC-39) containing both an EcoRI site (underlined) and the initiation codon (bold) and a reverse primer (59-GG GGT ACC TTA ACC AGA TTT GAA CAG AAG AAT G-39) containing both a KpnI site (underlined) and the stop codon (bold). The PCR product was purified, digested with restriction enzymes EcoRI and KpnI, and cloned into the corresponding sites of the pCBA-M vector.…”
Section: Construction Of Lc8 Expression Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…By maintaining LC8 in the reduced state, TRP14 prevents cytosolic activation of NF-jB. Exposure to oxidants or treatment with TNFa, IL-1, or LPS known to signal via H 2 O 2 production leads to the formation of LC8 dimers in which two molecules are linked via a disulfide bridge (515), resulting in its dissociation from IjB (224,227). This mode of redox-dependent inhibition of protein activities by interaction with binding partners is analogous to the association of Trx to ASK-1, an upstream activator of the c-Jun N-terminal kinase (INK) and p-38 MAPK signaling pathways (415) (Fig.…”
Section: Brigelius-flohé and Flohémentioning
confidence: 99%